Efektivitas Penagihan Pajak terhadap Pencairan Piutang Pajak - Putra, Fery Triastanto; Hartini, Hartini (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to determine the level of effectiveness of tax collection on tax receivables at the Kuningan Pratama Tax Service Office and this research is to determine effective actions in the context of disbursing tax receivables at the Kuningan Pratama Tax Service Office. This type of research uses a descriptive analysis method. The research subject is the Kuningan Pratama Tax Service Office located at JL. Aruji Kartawinata No.29 Kuningan in the period 2019 to 2022. The object of research is a series of billing actions. The data used by researchers in this study are primary data and secondary data. In this study, primary data were obtained by researchers through interviews with bailiff officers at the Kuningan Pratama Tax Service Office and in this study secondary data were obtained from administrative records of the Assessment and Collection Examination Section at the Kuningan Primary Tax Service Office. The results of this study indicate that the most effective collection activity in the context of disbursing tax receivables at the Kuningan Pratama Tax Service Office is by issuing a Distress Warrant. With a Distress Warrant, the average ratio of the effectiveness of tax collection to the disbursement of tax receivables during the period 2019 to 2022 is 16.42%.